Proceedings of the 25th ACM International Symposium on High-Performance Parallel and Distributed Computing 2016
DOI: 10.1145/2907294.2907311
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Execution Profiles

Abstract: Observing the relative behavior of an application's threads is critical to identifying performance bottlenecks and understanding their root causes. We present parallel execution profiles (PEPs), which capture the relative behavior of parallel threads in terms of the user selected code regions they execute. The user annotates the program to identify code regions of interest. The PEP divides the execution time of a multithreaded application into time intervals or a sequence of frames during which the code region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Stragglers can occur due to information obfuscation at different levels of the system. Literature [43] [14] [45] [95] has identified that information can be hidden at two different levels: i) OS Level and ii) Application Level. During the execution of resources, the master node (controller) hides information from workers (cluster nodes) at OS level.…”
Section: Data Abstractionmentioning
confidence: 99%
“…Stragglers can occur due to information obfuscation at different levels of the system. Literature [43] [14] [45] [95] has identified that information can be hidden at two different levels: i) OS Level and ii) Application Level. During the execution of resources, the master node (controller) hides information from workers (cluster nodes) at OS level.…”
Section: Data Abstractionmentioning
confidence: 99%